Coronary artery embolism and myocardial infarction, a case report - Narváez Orozco, Alejandro (2024)
Coronary embolism (CE) is a rare cause of non-atherosclerotic acute coronary syndrome (ACS). The clinical presentation is similar to ACS, and the diagnosis is supported by Shibata criteria. Atrial fibrillation is the main reported etiology in CE cases. Management includes percutaneous intervention with thromboaspiration and anticoagulation. The following case is a description of a patient with acute chest pain and recently diagnosed atrial fibrillation with a rapid ventricular response, is described. A thrombotic lesion in the distal right coronary artery of embolic origin, was documented. Successful mechanical thromboaspiration was performed; intravascular ultrasound showed no thrombus, dissection, or atherosclerotic plaque. CE is an underdiagnosed cause of ACS; diagnosis relies on Shibata criteria, and patients experience worse outcomes in follow-up.